Pengaruh Konservatisme Akuntansi, Struktur Modal, Likuiditas Terhadap Kualitas Laba - Utama, Girindra Astha Anggara Cahya; Hariyono, Anwar (Journal of Culture Accounting and Auditing, 2024)
This study aims to examine and analyze the effect of accounting conservatism, capital structure, liquidity on earnings quality. This type of research is quantitative research. The sampling method in this study was purposive sampling method. The sample for this study uses manufacturing companies in the consumer goods industry sector which are listed on the Indonesia Stock Exchange (IDX) for 2019-2021 with 108 data samples. The analytical method used is multiple linear regression analysis using the IBM SPSS statistics 22 program. The results show that accounting conservatism and capital structure variables have a positive effect on earnings quality. Meanwhile, the variable liquidity has no effect on earnings quality.